Time-resolved fluorescence microscopy in high-resolution brain imaging - Rusakov, Dmitri (Henry Stewart Talks, 2024)
Measuring intracellular [Ca2+], Ratiometric indicators in brain tissue, Fluorescence lifetime imaging (FLIM), Monitoring Ca2+ landscapes, Fast FLIM, Time-resolved fluorescence anisotropy imaging (TR-FAIM)